2018
DOI: 10.1002/cpcb.80
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Secretory Cargo Transport in Budding Yeast

Abstract: Budding yeast is an excellent model organism for studying the dynamics of the Golgi apparatus. To characterize Golgi function, it is important to visualize secretory cargo as it traverses the secretory pathway. We describe a recently developed approach that generates fluorescent protein aggregates in the lumen of the yeast endoplasmic reticulum and allows the fluorescent cargo to be solubilized for transport through the Golgi by addition of a small-molecule ligand. We further describe how to generate a yeast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…To create a wave of fluorescent vacuolar cargo, we modified a recently developed regulatable fluorescent secretory cargo ( Casler and Glick, 2019 ; Casler et al, 2019 ). Our secretory cargo consists of the tetrameric red fluorescent protein DsRed-Express2 fused to a dimerizing variant of FKBP, with a cleavable N-terminal signal sequence to direct cotranslational translocation into the ER.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To create a wave of fluorescent vacuolar cargo, we modified a recently developed regulatable fluorescent secretory cargo ( Casler and Glick, 2019 ; Casler et al, 2019 ). Our secretory cargo consists of the tetrameric red fluorescent protein DsRed-Express2 fused to a dimerizing variant of FKBP, with a cleavable N-terminal signal sequence to direct cotranslational translocation into the ER.…”
Section: Resultsmentioning
confidence: 99%
“…AP-1 was originally proposed to mediate transport of proteins from the TGN to endosomes (reviewed in Hinners and Tooze, 2003 ), but subsequent work implicated GGAs in TGN-to-endosome traffic in both yeast and mammalian cells ( Black and Pelham, 2000 ; Dell'Angelica et al, 2000 ; Hirst et al, 2000 ; Zhdankina et al, 2001 ). In S. cerevisiae , AP-1 localizes exclusively to the late Golgi, and it mediates intra-Golgi recycling of some resident late Golgi proteins and secretory cargoes ( Casler and Glick, 2019 ; Day et al, 2018 ; Liu et al, 2008 ; Papanikou et al, 2015 ; Spang, 2015 ; Valdivia et al, 2002 ). It was previously reported that yeast GGAs function upstream of AP-1 and that GGAs display similar kinetics of arrival and departure as the late Golgi reference marker Sec7 ( Daboussi et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach required overcoming a series of technical hurdles to ensure that the fluorescent secretory cargo reaches the ER lumen, that the cargo aggregates dissolve efficiently, and that the cargo traverses the secretory pathway without being diverted to the vacuole (Casler and Glick, 2018). A key step was to add a tripeptide ER export signal to the cargo (Nam et al, 2014; Yin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%